Characterization of tin dioxide (SnO2) based heterojunction and its optical response property - Chan, Weng Cheong. (2009)
n-SnO2/p-Si heterojunction and SnO2 thin film on quartz have been fabricated by a low cost sol-gel technique. The characterzation of pure SnO2 thin film and SnO2 doped with Magnesium (Mg, p-type dopant) and Antimony, (Sb, n-type dopant) have been investigated in detailed. Structure and microstructure of SnO2 thin film have been investigated by X-ray Diffraction, Scanning Electron Microscopy and Energy Dispersive X-ray with influence by different annealing temperatures. Structure of SnO2 doped with different concentration of Mg is also investigated in detailed. The XRD peak results were obtained and compared with the Join Committee on Powder Diffraction Standard (JCPDS) data. Full Width at Half Maximum (FWHM), grain size, and d-spacing at peak (211) were calculated for SnO2 thin film with the annealing temperatures increased from 400˚C to 800˚C. In addition, investigation of band gap SnO2 with effect of different annealing temperatures would be analyzed. Band gap engineering would be investigated in detailed by SnO2 doped with Mg dopant with the annealing temperatures increased in comparison with pure SnO2. Optical band gap of SnO2 doped with Sb dopant is also analyzed to prove the Burstein Moss shift theory. Band gap was investigated by optical methods, Ellipsometry and UV Visible Spectrometer. Lastly, electrical characterization such as I-V characteristic has been carried out on pure SnO2/p-Si heterojunction and effect of SnO2 doped with Mg dopant to the I-V curve. Turn on voltage and reverse saturation current would be analyzed in comparison between SnO2/p-Si heterojunction and effect of SnO2 doped with Mg dopant.